The Relationship between Knowledge and HIV/Aids Prevention Behavior At the Ngalum Putra Dormitory Students in the Pegunungan Bintang in Jayapura, Papua - Romantir, Ria; Yunita Mangonto; Muammar Karim; Albertho Siktaop; Wellem Duwiri; Yokbet Tepmul (PT. Intelek Cendikiawan Nusantara, 2024)
The whole world is still faced with the same problem, namely HIV/AIDS. Human Immunodeficiency Virus (HIV) is a virus that attacks the body's immune system. The Papua Provincial Health Service noted that there were 18,471 cases of HIV/AIDS sufferers as of September 30 2023 in Papua Province, and 20,726 cases in Central Papua Province. From the statement above, it is clear that the prevalence of HIV/AIDS cases in Indonesia, especially in Papua, is still a problem that has not been resolved to date. This study aims to determine the relationship between knowledge and HIV/AIDS prevention behavior among students at the Ngalum Putra Mountains Bintang Dormitory in Jayapura. The sample consisted of 20 students who lived in dormitories. Data collection used a questionnaire with 21 questions. The data obtained will be tested using the Sommers statistical test. Results were obtained with a significance of 0.00 < 0.05, which means that the Knowledge variable has a meaningful relationship and a close relationship of 1.00 was also obtained, which is in the perfect category. The relationship between the two variables has a positive correlation direction, which means that the higher the level of knowledge a student has, the higher the prevention behavior related to HIV AIDS will be obtained.